Building better science-policy interfaces for international environmental governance: Assessing potential within the Intergovernmental Platform for Biodiversity and Ecosystem Services (2012)
This article addresses implementation failure in international environmental governance by considering how different institutional configurations for linking scientific and policy-making processes may help to improve implementation of policies set out in international environmental agreements. While institutional arrangements for interfacing scientific and policy-making processes are emerging as key elements in the structure of international environmental governance, formal understanding regarding their effectiveness is still limited. In an effort to advance that understanding, we propose that science-policy interfaces can be understood as institutions and that implementation failures in international environmental governance may be attributed, in part, to institutional mismatches (sic. Young in Institutions and environmental change: Principal findings, applications, and research, MIT Press, Cambridge 2008) associated with poor design of these institutions. In order to investigate this proposition, we employ three analytical categories—credibility, relevance and legitimacy, drawn from Cash et al. Proc Natl Acad Sci 100(14):8086–8091, (2003), to explore basic characteristics of the institutions proscribed under two approaches to institutional design, which we term linear and collaborative. We then proceed to take a closer look at institutional mismatches that may arise with the operationalisation of the soon to be established Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES). We find that, while there are encouraging signs that institutions based on new agreements, such as the IPBES, have the potential to overcome many of the institutional mismatches we have identified, there remain substantial tensions between continuing reliance on the established linear approach and an emerging collaborative approach, which can be expected to continue undermining the credibility, relevance and legitimacy of these institutions, at least in the near future.